The Gender Pay Gap in Ireland from Austerity through Recovery - Karina Doorley; Ivan Privalko; Helen Russell; Dora Tuda (Institute of Labor Economics (IZA), 2021)
This paper estimates the raw and adjusted gender pay gap in Ireland between 2011 and 2018, a period of austerity measures and recovery from the Great Recession. Using survey data sources linked to administrative information on earnings, we show that the raw gender wage gap across the wage distribution has not changed much over this period: it is larger for higher earners and is mainly concentrated in the private sector. Using a Distribution Regression method, we estimate the relative contributions of explained and unexplained components to the overall gender wage gap at each point at the wage distribution and summarise the findings by wage quantile. The explained gender wage gap is negative, indicating that women have better labour market characteristics than men, on average. The unexplained gender wage gap is positive and increases with the wage level. This results in a small or zero gender wage gap at the bottom of the wage distribution which rises to 10% at the top of the wage distribution. The stability of the gender pay gap across the wage distribution in the private sector over the period suggest the strong structural inequalities, that are unlikely to change without significant interventions
Keywords: J31; J71; D31; 330; gender pay gap; occupational segregation; discrimination; Ireland